A NEW SPECIES OF PHYSETOPODA FROM SOUTH-EASTERN SPAIN (HYMENOPTERA, MUTILLIDAE) - Lo Cascio, Pietro; Grita, Flavia (Fragmenta entomologica, 2010)
Physetopoda romanoi n. sp. is described on the basis of female specimens collected on SE Spain and belonging to the Suárez’ collection. The new species is closely related to P. sericeiceps (André, 1901), from which differs mainly in the shape of head, eyes and scutellar scale, as well as in the punctuation pattern on the genae.